Suplementasi Tepung Ubi Jalar Kuning (Ipomoea batatas L) Sebagai Prebiotik Dalam Pakan Terhadap Kesehatan Ikan Lele Sangkuriang (Clarias gariepinus) - Liana, Liana; Agustina, Agustina; Kusdianto, Heru (Universitas Batangahari Jambi, 2024)
Feeding management is a very important factor in fish farming activities. Adding prebiotics to feed is an effort to increase the availability of nutrients in feed and fish health. This study aimed to determine the effect of sweet potato flour in feed on hematological parameters and nutritional coefficient values of sangkuriang catfish. This study used a completely randomized design (CRD) with 4 treatments 3 repetitions with the dose of each treatment, namely treatment 1 (0% sweet potato flour in feed), treatment 2 (1% sweet potato flour in feed), treatment 3 (2% sweet potato flour in feed), and treatment 4 (3% sweet potato flour in feed). Maintenance is carried out in a plastic container with a volume of 25 liters of water for 30 days. Feeding according to treatment was carried out three times a day in the morning, afternoon and evening using the at satiation method. The results showed that the provision of sweet potato flour in feed could increase the hematological parameters and nutritional coefficient values and gave the best value at P3 for the hemoglobin level parameter, namely 8.40; hematocrit level with a value of 79.01%; total leukocytes with a value of 75.23 Ã— 103 cells/mm3 and total erythrocytes with a value of 2.89 Ã— 106 cells/mm3 . In the nutritional coefficient value parameter, the best results are found in P3 with a total of 0.82.Â